Analisis Kemampuan Dan Kemauan Membayar (ATP-WTP) Pengunjung Situs Gunung Padang Kabupaten Cianjur - Norman Wardana; Aa Permana; Raden Rizki Muttaqien (PT. Hasba Edukasi Mandiri, 2025)
This study aims to explore the relationship between the ability to pay and the willingness to pay of visitors to the Gunung Padang site in Cianjur Regency. The issue addressed in this research focuses on the discrepancy between the financial capacity of visitors and the ticket price they are willing to pay, which may affect the effectiveness of management and the sustainability of the tourist destination. The research methodology uses a quantitative approach with data collection through surveys, utilizing a questionnaire instrument distributed to visitors. The results of the study indicate that the visitors' ability to pay is higher than their willingness to pay. This finding is influenced by several factors, such as limited facility quality, a lack of visitor understanding of the historical value of the site, and comparisons with other tourist destinations that offer more comprehensive facilities. The study also highlights the importance of improving the quality of facilities and implementing more intensive promotional strategies to increase visitors' understanding of the site's significance, which in turn could enhance their willingness to pay. The contribution of this research is expected to provide guidance for destination managers in designing more effective policies and contribute to the development of knowledge in the field of tourism economics and cultural destination management.